Utilization of Nutmeg Shell Ash a Filler Substitution In The AC-WC Laston Mixed Layer - Andika Khairil; Kurniasari Febrina Dian; Putra M. Izwan; Yusdi; Iqbal Muhammad; Saputra Romi; Mahyar Herri (E3S Web of Conferences, 2024)
Most of the road pavement construction used in Indonesia is flexible pavement where the material consists of coarse aggregate, fine aggregate, filler and asphalt. Currently, the fillers that are often used are rock ash, portland cement and lime. However, the filler used from these materials is relatively expensive, so there is a need for new innovations by using alternative materials that are more economical by utilizing community production waste materials in the form of nutmeg shell ash (ACP) produced from the process of burning nutmeg shells as filler. This research was conducted to determine the compressive strength of asphalt against the substitution of nutmeg shell ash (ACP) in the asphalt mixture as a partial replacement for cement with a percentage of 0%, 15%, 25%, 50%, 75%, and 100% with the number of objects The planned tests in this researchs were 75 specimen weighting 1.200 grams/specimen. The results showed that the best composition for substitution of nutmeg shell ash (ACP) and portland cement (PC) at a composition of 15% ACP and 85% PC from the results of the study obtained a stability value of 929.04 kg and Bina Marga specifications ≥ 800 kg